Analisis Pengaruh Variasi Susunan Laminasi dan Penambahan Fly Ash Terhadap Kekuatan Bending Komposit Hybrid Berpenguat Serat Daun Nanas-Woven Roving Fiberglass - Siti Annuriyah; Wiwik Dwi Pratiwi; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
The supply of pineapple leaf waste has great potential to provide benefits, other than just being composted or burned. Instead, the process will have an impact on humans and the environment. In addition, the handling of fly ash waste has also recently become a concern. The abundance of them and the lack of utilization add to the series of waste handling problems. Composite technology is one of the waste control solutions. Composite technology helps in the use of wastes as composite materials into new materials, especially in the shipping sector and generally for application in other industrial fields. This research aims to determine the effect of laminate configuration and fly ash substitution on the bending strength of the pineapple leaf fiber-reinforced hybrid composite WR200 as an alternative hull material. The configuration of the laminate was varied, and the effect of the substitution of fly ash as a filler on the composite was also analyzed. The variations used in this study are laminated configurations with fly ash substitution and without fly ash substitution. Composite samples were manufactured using the hand lay-up method with a reinforcement: matrix composition of 30%:70 %. The resulting composite with the highest bending strength of 120.47 MPa in the CWWC laminate configuration without fly ash substitution. The resulting composite can be applied as an accommodation room bulkhead material according to the SNI 01-4449-2006 standard.